ROLE OF VIRECHAN AND TAKRADHARA IN A CASE OF PRURIGO NODULARIS - Pabitra Kumar, Bera; Pulak Kanti, Kar (International Journal of Ayurveda and Pharma Research, 2015)
Clinically, Prurigo Nodularis (i.e. Chronic circumscribed nodular/ lichenification or pickers nodule) is a chronic, severe itch accompanied by 1 to 5 cm hard, nodules with smooth or warty surface surrounded by hyper pigmentation. The new lesions are usually red and inflamed whereas old lesions are pigmented. The lesion may also be excoriated. The lesion are mostly located in extensor surface of limbs, but they can be located on face and trunk. Among all types of skin disorder, it is the most severe form of prurigo, having very poor prognosis. In Ayurveda, no typical nomenclature has been found for the said diseases but considering all signs and symptoms of the diseases, it can be treated as Tridosaja kustha roga specially having Vatakapha predominance. In a case of Prurigo nodularis, Virechan and Takradhara was administered in a specific schedule for three months. After administration of Virechan and Takradhara for consecutive three months, it is found that nodules become almost thin and pruritus become completely absent. After four months of completion of the study, the skin color become almost normal. From this result, the authors had tried the same protocol in other three cases of prurigo nodularis which is also very significant. Further study should be carried out in a large sample to establish the role of said therapy on this particular disease.